2016
DOI: 10.1007/s10561-016-9553-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression and ultrastructural alterations in fresh-frozen, freeze-dried and γ-irradiated human amniotic membranes

Abstract: The aim of this work was to compare the effects on human amniotic membrane of freeze-drying and c-irradiation at doses of 10, 20 and 30 kGy, with freezing. For this purpose, nine cytokines (interleukin 10, platelet-derived growth factor-AA, plateletderived growth factor-BB, basic fibroblast growth factor, epidermal growth factor, transforming growth factor beta 1, and tissue inhibitors of metalloproteinase-1, -2, and -4) were titrated in 5 different preparations for each of 3 amniotic membranes included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 40 publications
1
43
0
2
Order By: Relevance
“…3033 Endogenous cytokine and growth factor levels (tissue inhibitor of metallo-proteinases, platelet derived growth factor, epidermal growth factor, fibroblast growth factor) are also affected at gamma doses as low as 10 kGy. 34 The superior healing observed in diabetic wounds treated by dHACA may support the advantage of aseptic processing. However, more scientific studies are needed to determine how terminal sterilization affects cellular mechanisms versus aseptic processing once the graft has been placed in a wound, as well as translation of those effects into healing metrics.…”
Section: Discussionmentioning
confidence: 96%
“…3033 Endogenous cytokine and growth factor levels (tissue inhibitor of metallo-proteinases, platelet derived growth factor, epidermal growth factor, fibroblast growth factor) are also affected at gamma doses as low as 10 kGy. 34 The superior healing observed in diabetic wounds treated by dHACA may support the advantage of aseptic processing. However, more scientific studies are needed to determine how terminal sterilization affects cellular mechanisms versus aseptic processing once the graft has been placed in a wound, as well as translation of those effects into healing metrics.…”
Section: Discussionmentioning
confidence: 96%
“…Placental tissues are processed in various ways, including: cryopreservation, hypothermic storage, and dehydration . Composition and processing alters the proteomic composition and may consequently affect how the grafts function …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Composition and processing alters the proteomic composition and may consequently affect how the grafts function. 9,[12][13][14][15] There are several beneficial properties that placental membranes natively possess that may support wound healing. In addition to acting as a protective physical covering, placental membranes have been reported to contain a wide variety of growth factors and cytokines, 13 which have been shown to promote beneficial cellular processes in vitro.…”
mentioning
confidence: 99%
“…Both Rodríguez-Ares et al 25 and Thomasen et al 24 have reported decreased protein content in dehydrated amnion as compared with cryopreserved amnion. 40 Commercial placental tissue allografts are regulated by the Federal Food and Drug Administration as human cell, tissue, and cellular and tissue-based products as defined in 21 CFR Part 1271 and Section 361 of the Public Health Services Act, which do not require premarket approval. Cooke et al 27 showed that ECM structure was compromised in dehydrated amnion as compared with cryopreserved amnion, that dehydrated amnion contained lower levels of hyaluronic acid, and that dehydrated amnion lacked high-molecularweight hyaluronic acid altogether.…”
Section: Discussionmentioning
confidence: 99%